The Concept of the millet in Turkish dictionaries: Its alteration and the impact on Ottoman Macedonia - Pandevska, Maria; Mitrova, Makedonka (Balcanica Posnaniensia. Acta et studia, 2020)
In the 19th century the dictionaries/glossaries represent the first brace which connected different cultures and languages, thus also linking the Orient with the Occident and vice versa. In this context the research is focused on the Turkish dictionaries/glossaries, which for a long time actually represented one of the basic media of transmitting the new Western ideas in the East, and in our case, in the Ottoman Empire. Through the short comparative analyses of these dictionaries/glossaries and their authors (from the 19th century and early 20th century) we follow the change of the cognitive concept of the term millet with the term nation. The case study is focused on Ottoman Macedonia and on the political implications caused by this change of the meaning of the Ottoman term millet.